Integrating Demand and Inventory Planning to Enhance Service Level: A Case Study in a Peruvian Craft Beer SME - Burga Lozada, Maria Paz (2025)
The study examines a craft beer SME, proposing a service management model using Demand Forecasting, Inventory Policy, and Supplier Management. It fills a Research Gap in applying these tools to improve demand forecasting and inventory management in Peruvian SMEs. The company faced logistical challenges impacting efficiency and competitiveness, which were mitigated through the model’s implementation. Results showed a 77% compliance in scheduled deliveries, optimizing the supply chain and operational efficiency. The study contributes academically by providing logistics models for the beverage sector and socioeconomically by enhancing SME competitiveness. Further applications in other contexts are recommended.